2012
DOI: 10.1038/jp.2012.100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of delivery room temperature on the admission temperature of premature infants: a randomized controlled trial

Abstract: Increasing delivery room temperatures to that recommended by the World Health Organization decreases cold stress in premature newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 17 publications
(20 reference statements)
2
44
0
8
Order By: Relevance
“…1,2 Additional techniques aimed at preventing heat loss in very preterm infants in the DR have been studied. These have included increasing the DR temperature, 3 occlusive wrapping, [4][5][6] exothermic mattresses 7,8 and polyethylene caps. 9 In clinical trials, each of these interventions increased mean admission temperature compared with conventional care, but many infants had admission temperatures outside the normal range despite these measures.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Additional techniques aimed at preventing heat loss in very preterm infants in the DR have been studied. These have included increasing the DR temperature, 3 occlusive wrapping, [4][5][6] exothermic mattresses 7,8 and polyethylene caps. 9 In clinical trials, each of these interventions increased mean admission temperature compared with conventional care, but many infants had admission temperatures outside the normal range despite these measures.…”
Section: Discussionmentioning
confidence: 99%
“…16,18 Suhu ruang operasi hangat (25,1 0 C) menjelang kelahiran BKB usia ≤32 minggu akan berpengaruh positif terhadap kenaikan suhu bayi 0,5 0 C lebih tinggi dibandingkan suhu ruang persalinan standar (22,5 0 C). 5,19 Terdapat perbedaan pengaruh antara pengaturan suhu ruang operasi 24 Hasil penelitian juga menunjukkan penurunan angka kejadian hipotermia menjadi 76, 7% dari 93,3% saat dilahirkan pada suhu ruang operasi 24 0 -26 0 C. Hasil ini sesuai dengan teori tentang perpindahan panas secara konveksi dan konduksi yang dipengaruhi oleh perbedaan suhu, suhu lingkungan atau ruangan yang hangat akan menurunkan perbedaan suhu antara bayi dan lingkungan sehingga mengurangi laju perpindahan panas tersebut. 15,16,18 Angka kejadian hipotermia yang tinggi pada dua kelompok penelitian (76, 7% vs 93,3%) menunjukkan manajemen termoregulasi pada BKB berat lahir rendah belum optimal.…”
Section: Pembahasanunclassified
“…Hal tersebut menyebabkan BKB rentan kehilangan panas tubuh dan produksi panas yang tidak adekuat menyebabkan terjadi hipotermia. [3][4][5]7 Upaya mencegah atau menurunkan angka kejadian hipotermia pada BKB sangat penting untuk menurunkan angka mortalitas. Organisasi WHO memberikan rekomendasi suhu ruang bersalin minimal 25 0 C yang terbukti menurunkan angka kejadian hipotermia.…”
unclassified
See 1 more Smart Citation
“…18 This proved to be an impossible task to accomplish; therefore, we analyzed delivery room temperature as a covariate and found that although the plastic bags increased admission temperatures, a warmer delivery room increased the effect. Although this simple intervention has been found to work in increasing core body temperature in premature infants, 19 clinicians are not consistent in increasing delivery room temperature. If effort is made to adjust the delivery room ambient air temperature prior to each delivery, along with implementing other thermal stability interventions, it is possible to completely eliminate the incidence of hypothermia as one group did in a quality improvement project over several years.…”
Section: Delivery Room Temperaturementioning
confidence: 99%